Associação Brasileira de Hematologia, Hematologia, Hemoterapia e Terapia Celular Consensus on genetically modified cells. Review article: Cell therapy in solid tumors - Nardo, Mirella; Motta, Tatiane C.; Colli, Leandro M.; Avanzi, Mauro P. (Hematology, Transfusion and Cell Therapy, 2021)
The use of immunotherapy in cancer treatment over the past decade has resulted in significant advances and improvements in cancer patients survival with the use of checkpoint inhibitors. Nevertheless, only a fraction of solid tumors responds to this immunotherapy modality. Another modality of immunotherapy consists of employing cell-based therapy as an adoptive therapeutic modality. That involves distinct modalities of cellular therapies such as CAR T cells (chimeric antigen receptor T cell), TILs (tumor-infiltrating lymphocytes), and TCR T cells. Those treatments have proven effective in hematologic tumors and could have an impact in tumors that do not respond to checkpoint inhibitors. This review aims to outline the rationale, operation, clinical applicability, and results of adoptive cell therapy for patients with solid tumors.